Comparison of the Effectiveness of Phosphorus 32 Application and 10 Mg/Cc Triamcinolone Acetonide Intralesional Injection on Keloid - Hani Indrayati; Jono Hadi Agusni; Asmaja Soedarwoto; Achmad Hussein S. Kartamihardja (International Journal of Integrated Health Sciences, 2016)
Objective: To analyze the effectiveness of phosphorus 32 (32P) application compared to 10 mg/cc triamcinolone acetonide (TA) intralesional injection in keloid.Methods: A single blind (evaluator blind) randomized clinical trial on 52 keloids was conducted during the period of May – August 2014 in Tumor and Skin Surgery Clinic, Department of Dermatovenereology and Department of Nuclear Medicine and Molecular Imaging, Dr. Hasan Sadikin General Hospital Bandung.Results: Lesions were divided into two groups with each group consisted of 26 lesions. Group A was treated with 32P application whereas group B was treated with 10 mg/cc TA intralesional injection. Flattening of the lesion of more than 50% was higher in the group treated with 32P application (76.9%) compared to the group that was treated with 10 mg/cc TA intralesional injection (57.7%) on the 8th week, but the difference was not statistically significant (p>0.05).Conclusions: Based on the statistical analysis, the application of 32P was as effective as the intralesional injection of 10 mg/cc TA for keloid lesions.Keywords: Flattening, keloid, phosphorus 32, triamcinolone acetonide DOI: 10.15850/ijihs.v4n1.683